The Bahamas : 2010 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
The Bahamas depends heavily on tourism and financial services. Executive Directors have commended the strong track record of prudent macroeconomic management, but have encouraged the government to broaden the domestic tax base, reduce distortions, increase the resilience of revenues to shocks, and specify contingency measures to reign in the growth in public debt. Greater transparency will underpin the medium-term fiscal strategy, and a higher international reserve coverage will help reduce vulnerabilities. Measures under way to strengthen the financial system have been commended.